The natural approach to adult learning and teaching of L2 grammar - Scheffler, Paweł (My University, 2008)
Learning a language in a natural way is normally understood to involve the development of implicit knowledge of that language. The acquisition of such knowledge takes place through communication and is driven by learnerinternal mechanisms which cannot be directly influenced by formal instruction. In the case of foreign or second language (L2) learning, the role of instruction is, then, to provide learners with opportunities for communication, and with assistance in those areas in which implicit learning is impossible or inefficient. This article argues that in the case of adult L2 learners the term “natural learning” should be interpreted as referring to explicit learning. This means that adult L2 instruction should primarily aim to engage the learners’ problem solving mechanism by providing them with explicit rules about the target code, and then with opportunities for proceduralizing and automatizing those rules. L2 acquisition is thus treated as the acquisition of a complex skill.
Keywords: explicit grammar knowledge; explicit foreign language learning; Second Language Acquisition; English grammar learning